TEATRO Y TEATRO FRANCÉS TRADUCIDO EN EL MADRID DE 1808: UNA APROXIMACIÓN - Saura Sánchez, Alfonso (Anales de Filología Francesa, 2008)
On May 2nd, 1808, the entrance doors of the public playhouses in Madrid remained shut. Simbolically, this closure also represented the end of a period in the Spanish dramatic scene, characterised by the crucial presence of a Baroque repertoire and the desire to introduce changes, mostly directed to the furthering of Neoclassical drama, supported by enlightened intellectuals who availed themselves of plays in translation. Aiming for objectivity, this study provides a list of premieres of the last seasons, with a view to make translations from the French stand out, in order to show that there was a considerable number of them. The ultimate aim is to discuss how far these translations of French pieces influenced the writing of new Spanish plays.